(untitled) (Revista Brasileira de Contabilidade e Gestão, 2013)
This paper is a report on the problems of literacy and the possibilities of use of informatics as a way to alleviate these problems. Based on these fundamentals, we developed the learning objects to assist in the acquisition of literacy. One of the objects uses the technique of recognition and sorting of letters. The other object applies to word formation with the ordering of syllables. Both objects are presented in this article. The end of the paper describes the experiences in applying these classes of objects in the second year of elementary school, in two separate semesters.